Pengaruh Ketersediaan Buku dan Fasilitas Ruang Baca Terhadap Minat Mahasiswa Mengunjungi Perpustakaan Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2024/2025 - Nafasati, Nandini Muqni; Ernajati, Justia (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to analyze the effect of book availability and reading room facilities on students' interest in visiting the library at Bhinneka PGRI University in Tulungagung. The research method used is quantitative. The data collection method used is a questionnaire in the form of a survey administered to 133 respondents. The analysis methods used were validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and determination coefficient. The analysis results showed that, partially, the availability of books significantly influenced the interest in visiting the library with a calculated t-value (8.161) > t-table (1.978) at a significance level of 0.000 < 0.05, so H1 was accepted and H0 was rejected. Reading room facilities also have a significant partial effect with a calculated t-value (11.371) > t-table (1.978) at a significance level of 0.000 < 0.05, so H2 is accepted and H0 is rejected. Simultaneously, book availability and reading room facilities significantly influence interest in visiting the library, with the calculated F value (69.074) > F table (3.07) at a significance level of 0.000 < 0.05, so H3 is accepted and H0 is rejected. The regression analysis results show that the constant is 16.818, with a regression coefficient of 0.179 for the availability of books and 0.579 for reading room facilities. Based on these results, it can be concluded that both the availability of books and reading room facilities have a significant partial and simultaneous effect on students' interest in visiting the library.